Fatigue damage assessment under random and variable amplitude multiaxial loading conditions in structural steels. (July 2017) - Anes, V.; Caxias, J.; Freitas, M.; Reis, L.
Highlights: A new procedure for evaluating fatigue damage assessment of multiaxial random loadings is proposed. Random and variable amplitude spectra are taken into account. A stress scale factor as a function of the stress amplitude ratio and stress level is employed. Structural steels data from experiments under different multiaxial loadings are presented. Abstract: Fatigue damage assessment of multiaxial random loadings is a complex issue and a subject of actual interest in mechanical design. In this work, the performance of the stress scale factor (SSF) criterion is evaluated under variable amplitude loading conditions, and damage accumulation approaches. This evaluation is performed by taking into account two types of loading spectra, namely the loading block spectra (where the loading pattern is well identified and repeated until rupture), and the random loading spectra (where the stochastic behaviour of the axial and shear loading components do not allow a direct identification of the loading pattern). Moreover, the validity of the hypothesis in which the SSF damage map remains valid for any high strength steel under variable amplitude loading conditions is also inspected by analysing fatigue life correlation of the 1050 QT steel and the 304L stainless steel under a multiaxial loading block.